Implementasi Model Problem-Based Learning dalam Meningkatkan Hasil Belajar Siswa pada Pembelajaran Dasar-Dasar Teknik Elektronika di SMK Negeri 2 Dumai - Diah Haryati; Hanesman Hanesman (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
The learning model that can be used to make students active is the Problem-Based Learning (PBL) model. The Problem-Based Learning model is a problem-based learning, where learning is centered on students so that students are required to provide solutions to the problems given. This study aims to determine how much impact the application of the PBL model has in improving student learning outcomes on learning the Basics of Electronic Engineering at SMK Negeri 2 Dumai. The type of research used is quantitative research with a quasi-experimental method using a pretest-posttest control group design. The research subjects consisted of 64 students divided into two groups, namely class X TEI SMK Negeri 2 Dumai as an experimental group that applies the PBL model (36 students) and class X TEI SMK Negeri 3 Dumai as a control group that applies the conventional learning model (28 students). The research instrument was a multiple-choice objective test of 25 items whose validity and reliability had been tested with a Cronbach's Alpha value of 0.843. The data analysis technique used descriptive statistics and Independent Samples T-Test. The results showed a significant difference in learning outcomes between the experimental and control classes, with a t-test value of 4.168 and a significance level of 0.000 (p < 0.05). The experimental class experienced an average increase in learning outcomes of 15.55 points (from 64.78 to 80.33), while the control class only increased by 7.57 points (from 63.43 to 71.00), with a posttest average difference of 9.333 points. Furthermore, the PBL model was also effective in reducing the ability gap between students, as indicated by a decrease in the standard deviation from 9.457 to 8.021. It can be concluded that the implementation of the PBL learning model has a significant impact on improving student learning outcomes in the Fundamentals of Electronic Engineering course at SMK Negeri 2 Dumai.